Geographic Mapping of Crohn’s Disease and Its Relation to Affluence in Jiangsu Province, an Eastern Coastal Province of China - Dong Hu; Jianan Ren; Gefei Wang; Guosheng Gu; Song Liu; Xiuwen Wu; Jun Chen; Huajian Ren; Zhiwu Hong; Jieshou Li (Gastroenterology Research and Practice)
Background. Geographical variation in the incidence of Crohn’s disease (CD) has been reported in Europe and North American. However, there are no comparable data in mainland China. Methods. We retrospectively identified incident cases of CD patients registered in Jinling hospital during 2003 to 2012. The standardized incidence ratio (SIR) was calculated for each area of Jiangsu province and a thematic map of CD was made according to the local SIR. The association between incidence and local economic status was revealed by correlation between SIR of CD and different local economic indicators. Results. A total of 653 CD patients (male-to-female ratio, 1.8 : 1) from Jiangsu province were included. A steady increase was observed in the number of CD patients over the period of observation. Disease map of SIR showed a pronounced geographic concentration of CD in the south part of Jiangsu province. Spearman correlation analysis showed a positive correlation between local SIR of CD and local economic indicators. Conclusions. There is a marked geographic variability in CD incidence across Jiangsu province. CD incidence in affluent areas seems to be higher than that in less affluent areas. Further multicenter population-based studies are needed to assess the real disease map of CD.